A kind of heterocyclic aramid fiber with high elongation and preparation method thereof

By reacting 4,4'-diaminodiphenyl ether, 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine with terephthalyl chloride, polymer spinning paste was prepared and heterocyclic aramid fibers with high elongation were obtained through a specific process, which solved the problem of difficult to take into account both the mechanical properties and elongation of the fibers in the prior art, and achieved significant improvement in fiber elongation and stability of product quality.

CN117418325BActive Publication Date: 2025-03-25SICHUAN PHAETON TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311618936.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-29
Publication Date
2025-03-25
Estimated Expiration
2043-11-29

AI Technical Summary

Technical Problem

In the prior art, the heat exchange efficiency of the liquid in the reactor is low, the heat distribution is uneven, the temperature adjustment control is slow, the product output is low, and automation work is difficult to achieve, resulting in difficult to take into account the mechanical properties and elongation of heterocyclic aramid fibers.

Method used

4,4'-diaminodiphenyl ether (4,4-ODA), 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and p-phenylenediamine (PPDA) were used as diamine monomers, and a new amide bond structural unit was generated by nucleophilic addition reaction with terephthalyl chloride (TPC), and polymer spinning slurry was prepared, and then a high elongation heterocyclic aramid fiber was obtained through filtration, defoaming, metering extrusion, solidification molding, plastic stretching, water washing and drying.

Benefits of technology

While ensuring the mechanical properties of fibers remain unchanged, the elongation of fibers is significantly improved, and the market application fields are expanded and the product quality is stable. It is of great significance to the development of the high-performance organic fiber manufacturing industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117418325B_ABST
    Figure CN117418325B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of high-performance organic fibers, and in particular to a heterocyclic aramid fiber with high elongation and a preparation method thereof, using 4,4'-diaminodiphenyl ether (4,4-ODA), 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and p-phenylenediamine (PPDA) as diamine monomers. While ensuring that the original mechanical properties of the fiber remain basically unchanged, the solid content of the polymerized spinning slurry can be increased while the elongation of the fiber can be greatly improved, so that the market application field of the heterocyclic aramid fiber can be expanded and the product quality can be stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-performance organic fibers, and in particular to a heterocyclic aramid fiber with high elongation and a preparation method thereof. Background Art

[0002] Heterocyclic aramid fiber refers to a type of para-aramid fiber containing aromatic heterocycles on the main chain, and the typical aromatic heterocycle is benzimidazole ring. According to theoretical calculations, the tensile strength of the fiber synthesized by ternary condensation of p-phenylenediamine, terephthaloyl chloride and benzimidazole diamine can reach 2.0-5.5GPa, and the elongation can reach 2.0%-4.6%. It also has high thermal stability, and the decomposition temperature of fully aromatic polyamide fiber can reach 550℃. As a reinforcement, the preparation of resin-based high-performance composite materials is one of the most important application areas of aramid. The application range of aramid-reinforced resin-based composite materials is very wide, and it plays an important role in many fields such as aerospace, military anti-bullet, sports equipment, automobiles and construction.

[0003] In order to obtain higher mechanical properties, heterocyclic aramid fibers need to prepare a polymer spinning slurry with a higher molecular weight and a consistent rigid chain structure. However, due to the higher molecular weight and rigid chain structure of the polymer spinning slurry, the fibers produced through a series of spinning processes show high strength but low elongation, and cannot take into account both strength and elasticity at the same time, which limits the application of the fibers in composite materials. Summary of the invention

[0004] The purpose of the present invention is to provide a heterocyclic aramid fiber with high elongation and a preparation method thereof, so as to solve the technical problems in the prior art of low heat exchange efficiency of the liquid in the reactor, uneven heat distribution, slow temperature adjustment control, low product output and difficulty in automation.

[0005] The invention discloses a method for preparing heterocyclic aramid fiber with high elongation, using 4,4'-diaminodiphenyl ether (4,4-ODA), 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and p-phenylenediamine (PPDA) as diamine monomers.

[0006] In the conventional polycondensation addition reaction of heterocyclic aramid resin, 4,4'-diaminodiphenyl ether (4,4-ODA) is used to replace a part of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and p-phenylenediamine (PPDA), and a nucleophilic addition reaction is carried out with terephthaloyl chloride (TPC) to generate a new amide bond structural unit. The prepared polymer spinning slurry has a higher molecular weight and reduces its original rigid chain structure ratio. The reaction equation includes the following two:

[0007] 1.H2N--ODA-NH2+Cl-OC-Ph-CO-Cl->H2N--ODA-NH-CO-Ph-CO-NH2+HCl

[0008] Among them, H2N--ODA-NH2 represents 4,4'-diaminodiphenyl ether, and Cl-OC-Ph-CO-Cl represents terephthaloyl chloride.

[0009] 2.H2N--Ph-NH2+Cl-OC-Ph-CO-Cl->H2N--Ph-NH-CO-Ph-CO-NH2+HCl

[0010] Here, Ph represents a phenyl group.

[0011] The specific reaction formula is:

[0012]

[0013] Further, the diamine monomer is dissolved in the solvent system under stirring at 30° C.-40° C. for 1-5 hours.

[0014] Furthermore, the solid content of the solvent system is controlled at 5-7%.

[0015] Furthermore, the molar ratio of the 4,4'-diaminodiphenyl ether (4,4-ODA) to 2-(4-aminophenyl)-5-aminobenzimidazole (R3) is ≤1, and the molar ratio of the 4,4'-diaminodiphenyl ether (4,4-ODA) to p-phenylenediamine (PPDA) is ≥1.

[0016] Furthermore, the diamine monomer is used to prepare a polymer spinning slurry.

[0017] Furthermore, the polymerized spinning slurry is filtered, degassed, metered extruded, coagulated, plasticized, stretched, washed and dried to obtain raw fibers.

[0018] Furthermore, the polymerized spinning slurry is stored in a storage tank under nitrogen protection.

[0019] Furthermore, the filtering is: filtering the polymerized spinning slurry through a 1-2 level 500-1000 g weight needle felt plate frame filter.

[0020] Furthermore, the degassing: the slurry is degassed using a vacuum umbrella plate tower degassing tower.

[0021] Furthermore, the metering extrusion: using a 1.5-5ccl micro-metering pump to extrude the polymer slurry from the spinneret.

[0022] Furthermore, the coagulation molding is as follows: the polymer slurry extruded from the spinneret is passed through a coagulation bath for molding, wherein the coagulation liquid in the coagulation bath is an aqueous solution containing 20%-50% DMAC.

[0023] Furthermore, the plasticizing and stretching: the nascent fibers are stretched by a pulling device while being coagulated and formed in a coagulation bath, with a stretching ratio of 20% to 110%.

[0024] Furthermore, the water washing: the as-spun fibers are washed by spraying with deionized water to remove DMAC, HCL and LiCl residues contained in the fibers.

[0025] Furthermore, the drying step comprises sending the cleaned spun fibers to a drying device through a traction roller, and controlling the drying temperature to be 90-150°C.

[0026] Furthermore, the raw fiber is subjected to heat treatment and high-multiple stretching to obtain a product.

[0027] Furthermore, the heat treatment high-multiple stretching: the dried virgin fiber is continuously fed into the heat treatment drying tunnel through the unwinding equipment, and the virgin fiber is heat-treated and stretched at a high multiple by utilizing the speed difference of the front and rear traction rollers of the heat treatment drying tunnel. Nitrogen is used to protect the interior of the heat treatment drying tunnel, the heat treatment temperature is controlled at 400-500°C, and the stretching ratio of the front and rear traction rollers is 30-60%.

[0028] Furthermore, the method for preparing the polymer spinning slurry comprises the following steps: preparing a solvent system, measuring the preparation amount, detecting the water content, dissolving the diamine monomer, cooling, prepolymerizing, tunning and neutralizing to reduce viscosity.

[0029] Furthermore, the solvent system is prepared by adding the dried LiCl solvent to the DMAC solvent at a content of 2.5%-3.5%.

[0030] Furthermore, the metered preparation amount: the preparation amount of a single polymerization reactor is 1000-5000L.

[0031] Furthermore, the cooling is as follows: cooling the dissolved but unpolymerized stock solution to below 3°C.

[0032] Furthermore, the prepolymerization: according to the reaction equation, 98.5% of the mass of terephthaloyl chloride (TPC) is added into the stock solution in an equal molar ratio to carry out a low-temperature polycondensation addition reaction.

[0033] Furthermore, the telomerization: the remaining about 1.5% by weight of terephthaloyl chloride (TPC) is added to the polymerization reaction in batches until the dynamic viscosity reaches 60,000-180,000 centibars.

[0034] Furthermore, the neutralization and viscosity reduction are as follows: 50%-100% of the theoretical mass of Ca(OH)2 (anhydrous calcium hydroxide) is added in batches according to the molar ratio of hydrogen chloride as a by-product of the polycondensation reaction, and the reaction is continued with stirring for 1 hour.

[0035] A heterocyclic aramid fiber with high elongation, characterized in that it is made by the above method.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1. The present invention can use 4,4'-diaminodiphenyl ether (4,4-ODA) to replace a part of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and p-phenylenediamine (PPDA) while ensuring that the original mechanical properties of the fiber remain basically unchanged, and conduct nucleophilic addition reaction with terephthaloyl chloride (TPC), thereby increasing and adjusting the sequence structure in the macromolecular chain, achieving the purpose of changing the molecular conjugated large л bond, thereby increasing the solid content of the polymerized spinning slurry and greatly improving the elongation of the fiber, expanding the market application field of heterocyclic aramid fiber, and stabilizing the product quality. It is of great significance to the development of the heterocyclic aramid fiber manufacturing industry and even the entire high-performance organic fiber manufacturing industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only represent some embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0039] Figure 1 The figure is a schematic diagram of the process of preparing the polymer spinning slurry of the present invention.

[0040] Figure 2 The figure is a schematic diagram of the preparation process of heterocyclic aramid fiber with high elongation according to the present invention. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0042] The performance parameters of aramid products on the market are as follows:

[0043]

[0044]

[0045] Example 1

[0046] This embodiment discloses a method for preparing heterocyclic aramid fiber with high elongation, comprising the following steps:

[0047] S1. Add 781 L of DMAC (dimethylacetamide) solvent with a water content of 101 ppm into a 1000 L polymerization reactor.

[0048] S2. LiCl (anhydrous lithium chloride) weighing 28.5 kg, which had been vacuum dried at 230° C. for 1 hour, was added into the polymerization kettle containing the solvent. That is, the content of LiCl (anhydrous lithium chloride) in the solvent system was about 3.5%.

[0049] S3. After stirring and dissolving in the polymerization kettle for 0.5 hour, the moisture content was tested and the moisture content was 275 ppm.

[0050] S4. According to the requirement of 5% solid content of polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and 4,4'-diaminodiphenyl ether (4,4-ODA) is 1:1. The material addition amount is calculated by the reaction equation, and 10.505 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and 9.379 kg of 4,4'-diaminodiphenyl ether (4,4-ODA) are added into the polymerization kettle.

[0051] S5. According to the requirement of 5% solid content of polymer material, the molar ratio of p-phenylenediamine (PPDA) to 4,4'-diaminodiphenyl ether (4,4-ODA) is 1:1. The material addition amount is calculated by the reaction equation. 5.066 kg of p-phenylenediamine (PPDA) is added to the polymerization kettle, and stirring and dissolving is started for 2-4 hours. The temperature of the polymerization kettle is controlled at 35°C.

[0052] S6. Cool the materials in the polymerization kettle through the polymerization kettle jacket to 0-5°C.

[0053] S7. According to the requirement of 5% solid content of the polymer material, the total amount of terephthaloyl chloride added is calculated by the reaction equation, and 98.5% of the theoretical total mass of terephthaloyl chloride (TPC), i.e. 28.133 kg, is added into the polymerization kettle for prepolymerization.

[0054] S8. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.428 kg, was added into the polymerization reactor in three portions to carry out telomerization reaction.

[0055] S9, sampling and testing, the dynamic viscosity is 65,000 centipoise.

[0056] S10. The output of the reaction by-product HCL was calculated according to the polymerization reaction equation, corresponding to the input of 7.22 kg of Ca(OH)2 (anhydrous calcium hydroxide). The reaction was continued with stirring for 0.5 hours. The dynamic viscosity was measured by sampling and the result was 61,000 centipoise.

[0057] S11, filtering and degassing the obtained polymer spinning slurry and then transferring it into a spinning section storage tank.

[0058] S12, the polymerized spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000 dtex, and then initially formed in a coagulation bath, and plasticized and stretched by a traction roller, with a stretching ratio of 30%, and the coagulation liquid is an aqueous solution with a DMAC content of 50%.

[0059] S13, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 140°C.

[0060] S14, the reeled nascent fibers continuously enter the heat treatment drying tunnel through the unwinder and the traction rollers, and the nascent fibers are heat-stretched by controlling the stretching ratio by traction before and after the heat treatment drying tunnel. The heat treatment drying tunnel is 10 meters long, the temperature is 450°C, and the spinning speed is 20 meters / minute. In the state where no filaments are generated, the maximum stretching ratio applied by the front and rear five rollers is 60%.

[0061] S15. After stretching, a finished fiber with a line density of 1005 dtex is obtained.

[0062] S16. The results of the test are shown in Table 1 below.

[0063] Table 1

[0064]

[0065] Example 2

[0066] In this embodiment, as a preferred embodiment of the present invention, a method for preparing heterocyclic aramid fiber with high elongation comprises the following steps:

[0067] S1. Add 781 L of DMAC (dimethylacetamide) solvent with a water content of 108 ppm into a 1000 L polymerization kettle.

[0068] S2. LiCl (anhydrous lithium chloride) weighing 28.5 kg, which had been vacuum dried at 230° C. for 1 hour, was added into the polymerization kettle containing the solvent. That is, the content of LiCl (anhydrous lithium chloride) in the solvent system was about 3.5%.

[0069] S3. After stirring and dissolving in the polymerization kettle for 0.5 hour, the moisture content was tested and the moisture content was 289 ppm.

[0070] S4. According to the requirement of 6% solid content of polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and 4,4'-diaminodiphenyl ether (4,4-ODA) is 1:1. The material addition amount is calculated by the reaction equation, and 12.711 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and 11.349 kg of 4,4'-diaminodiphenyl ether (4,4-ODA) are added to the polymerization kettle.

[0071] S5. According to the requirement of 6% solid content of polymer material, the molar ratio of p-phenylenediamine (PPDA) to 4,4'-diaminodiphenyl ether (4,4-ODA) is 1:1. The material addition amount is calculated by the reaction equation. 6.126 kg of p-phenylenediamine (PPDA) is added to the polymerization kettle, and stirring and dissolving is started for 2-4 hours. The temperature of the polymerization kettle is controlled at 35°C.

[0072] S6. Cool the materials in the polymerization kettle through the polymerization kettle jacket to 0-5°C.

[0073] S7. According to the requirement of 6% solid content of the polymer material, the total amount of terephthaloyl chloride added is calculated by the reaction equation, and 98.5% of the theoretical total mass of terephthaloyl chloride (TPC), i.e. 34.041 kg, is added into the polymerization kettle for prepolymerization.

[0074] S8. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.518 kg, was added into the polymerization reactor in three portions to carry out telomerization reaction.

[0075] S9, sampling and testing, the dynamic viscosity is 89,000 centipoise.

[0076] S10. Calculate the output of the reaction by-product HCL according to the polymerization reaction equation, corresponding to the input of 7.22 kg of Ca(OH)2 (anhydrous calcium hydroxide), continue stirring the reaction for 0.5 hours, and take a sample to detect the dynamic viscosity, which is 85,000 centipoise.

[0077] S11, filtering and degassing the obtained polymer spinning slurry and then transferring it into a spinning section storage tank.

[0078] S12, the polymerized spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000 dtex, and then initially formed in a coagulation bath, and plasticized and stretched by a traction roller, with a stretching ratio of 50%, and the coagulation liquid is an aqueous solution with a DMAC content of 50%.

[0079] S13, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 140°C.

[0080] S14, the wound spun fibers continuously enter the heat treatment drying tunnel through the unwinder and the traction rollers, and the spun fibers are heat-stretched by controlling the stretching ratio before and after the heat treatment drying tunnel. The heat treatment drying tunnel is 10 meters long, the temperature is 450°C, and the spinning speed is 20 meters / minute. In the state where no filaments are generated, the maximum stretching ratio applied by the front and rear five rollers is 50%.

[0081] S15. After stretching, a finished fiber with a line density of 1021 dtex is obtained.

[0082] S16. The results of the test are shown in Table 2 below.

[0083] Table 2

[0084]

[0085] Example 3

[0086] In this embodiment, as a preferred embodiment of the present invention, a method for preparing heterocyclic aramid fiber with high elongation comprises the following steps:

[0087] S1. Add 781 L of DMAC (dimethylacetamide) solvent having a water content of 121 ppm into a 1000 L polymerization reactor.

[0088] S2. LiCl (anhydrous lithium chloride) weighing 28.5 kg, which had been vacuum dried at 230° C. for 1 hour, was added into the polymerization kettle containing the solvent. That is, the content of LiCl (anhydrous lithium chloride) in the solvent system was about 3.5%.

[0089] S3. After stirring and dissolving in the polymerization kettle for 0.5 hour, the moisture content was tested and the moisture content was 266 ppm.

[0090] S4. According to the requirement of 7% solid content of polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and 4,4'-diaminodiphenyl ether (4,4-ODA) is 1:1. The material addition amount is calculated by the reaction equation, and 15.253 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and 13.619 kg of 4,4'-diaminodiphenyl ether (4,4-ODA) are added into the polymerization kettle.

[0091] S5. According to the requirement of 7% solid content of polymer material, the molar ratio of p-phenylenediamine (PPDA) to 4,4'-diaminodiphenyl ether (4,4-ODA) is 1:1. The material addition amount is calculated by the reaction equation. 7.35 kg of p-phenylenediamine (PPDA) is added to the polymerization kettle, and stirring and dissolving is started for 2-4 hours. The temperature of the polymerization kettle is controlled at 35°C.

[0092] S6. Cool the materials in the polymerization kettle through the polymerization kettle jacket to 0-5°C.

[0093] S7. According to the requirement of 7% solid content of the polymer material, the total amount of terephthaloyl chloride added is calculated by the reaction equation, and 98.5% of the theoretical total mass of terephthaloyl chloride (TPC), i.e. 40.849 kg, is added into the polymerization kettle for prepolymerization.

[0094] S8. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.622 kg, was added into the polymerization reactor in three portions to carry out telomerization reaction.

[0095] S9, sampling and testing, the dynamic viscosity is 113,000 centipoise.

[0096] S10. The output of the reaction by-product HCL was calculated according to the polymerization reaction equation, corresponding to the input of 8.66 kg of Ca(OH)2 (anhydrous calcium hydroxide). The reaction was continued with stirring for 0.5 hours. The dynamic viscosity was detected by sampling and was 98,000 centipoise.

[0097] S11, filtering and degassing the obtained polymer spinning slurry and then transferring it into a spinning section storage tank.

[0098] S12, the polymerized spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000dtex, and then initially formed in a coagulation bath, and plasticized and stretched by a traction roller, with a stretching ratio of 70%, and the coagulation liquid is an aqueous solution with a DMAC content of 50%.

[0099] S13, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 140°C.

[0100] S14, the reeled nascent fibers continuously enter the heat treatment drying tunnel through the unwinder and the traction rollers, and the nascent fibers are heat-stretched by controlling the stretching ratio by traction before and after the heat treatment drying tunnel. The length of the heat treatment drying tunnel is 10 meters, the temperature is 450°C, and the spinning speed is 20 meters / minute. In the state where no filaments are generated, the maximum stretching ratio applied by the front and rear five rollers is 45%.

[0101] S15. After stretching, a finished fiber with a line density of 1011 dtex is obtained.

[0102] S16. The test results are shown in Table 3 below.

[0103] Table 3

[0104]

[0105] Example 4

[0106] In this embodiment, as a preferred embodiment of the present invention, a method for preparing heterocyclic aramid fiber with high elongation comprises the following steps:

[0107] S1. Add 781 L of DMAC (dimethylacetamide) solvent with a water content of 101 ppm into a 1000 L polymerization reactor.

[0108] S2. LiCl (anhydrous lithium chloride) weighing 28.5 kg, which had been vacuum dried at 230° C. for 1 hour, was added into the polymerization kettle containing the solvent. That is, the content of LiCl (anhydrous lithium chloride) in the solvent system was about 3.5%.

[0109] S3. After stirring and dissolving in the polymerization kettle for 0.5 hour, the moisture content was tested and the moisture content was 286 ppm.

[0110] S4. According to the requirement of 7% solid content of polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) to 4,4'-diaminodiphenyl ether (4,4-ODA) is 2:1. The material addition amount is calculated by the reaction equation, and 19.067 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and 8.512 kg of 4,4'-diaminodiphenyl ether (4,4-ODA) are added into the polymerization kettle.

[0111] S5. According to the requirement of 7% solid content of polymer material, the molar ratio of p-phenylenediamine (PPDA) to 4,4'-diaminodiphenyl ether (4,4-ODA) is 1:1. The material addition amount is calculated by the reaction equation. 4.597 kg of p-phenylenediamine (PPDA) is added to the polymerization kettle, and stirring and dissolving is started for 2-4 hours. The temperature of the polymerization kettle is controlled at 35°C.

[0112] S6. Cool the materials in the polymerization kettle through the polymerization kettle jacket to 0-5°C.

[0113] S7. According to the requirement of 7% solid content of the polymer material, the total amount of terephthaloyl chloride added is calculated by the reaction equation, and 98.5% of the theoretical total mass of terephthaloyl chloride (TPC), i.e. 40.849 kg, is added into the polymerization kettle for prepolymerization.

[0114] S8. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.622 kg, was added into the polymerization reactor in three portions to carry out telomerization reaction.

[0115] S9, sampling and testing, the dynamic viscosity is 107,000 centipoise.

[0116] S10. Calculate the output of the reaction by-product HCL according to the polymerization reaction equation, corresponding to the input of 8.66 kg of Ca(OH)2 (anhydrous calcium hydroxide), continue stirring the reaction for 0.5 hours, and take a sample to detect the dynamic viscosity, which is 95,000 centipoise.

[0117] S11, filtering and degassing the obtained polymer spinning slurry and then transferring it into a spinning section storage tank.

[0118] S12, the polymerized spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000dtex, and then initially formed in a coagulation bath, and plasticized and stretched by a traction roller, with a stretching ratio of 90%, and the coagulation liquid is an aqueous solution with a DMAC content of 50%.

[0119] S13, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 140°C.

[0120] S14, the reeled nascent fibers continuously enter the heat treatment drying tunnel through the unwinder and the traction rollers, and the nascent fibers are heat-stretched by controlling the stretching ratio by traction before and after the heat treatment drying tunnel. The length of the heat treatment drying tunnel is 10 meters, the temperature is 450°C, and the spinning speed is 20 meters / minute. In the state where no filaments are generated, the maximum stretching ratio applied by the front and rear five rollers is 40%.

[0121] S15. After stretching, a finished fiber with a line density of 1007 dtex is obtained.

[0122] S16. The test results are shown in Table 4 below.

[0123] Table 4

[0124]

[0125] Example 5

[0126] In this embodiment, as a preferred embodiment of the present invention, a method for preparing heterocyclic aramid fiber with high elongation comprises the following steps:

[0127] S1. Add 781 L of DMAC (dimethylacetamide) solvent with a water content of 101 ppm into a 1000 L polymerization reactor.

[0128] S2. LiCl (anhydrous lithium chloride) weighing 28.5 kg, which had been vacuum dried at 230° C. for 1 hour, was added into the polymerization kettle containing the solvent. That is, the content of LiCl (anhydrous lithium chloride) in the solvent system was about 3.5%.

[0129] S3. After stirring and dissolving in the polymerization kettle for 0.5 hour, the moisture content was tested and the moisture content was 286 ppm.

[0130] S4. According to the requirement of 7% solid content of polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) to 4,4'-diaminodiphenyl ether (4,4-ODA) is 2:1. The material addition amount is calculated by the reaction equation, and 22.606 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and 10.092 kg of 4,4'-diaminodiphenyl ether (4,4-ODA) are added into the polymerization kettle.

[0131] S5. According to the requirement of 7% solid content of polymer material, the molar ratio of p-phenylenediamine (PPDA) to 4,4'-diaminodiphenyl ether (4,4-ODA) is 0.8:1. The material addition amount is calculated by the reaction equation. 4.360 kg of p-phenylenediamine (PPDA) is added to the polymerization kettle, and stirring and dissolving is started for 2-4 hours. The temperature of the polymerization kettle is controlled at 35°C.

[0132] S6. Cool the materials in the polymerization kettle through the polymerization kettle jacket to 0-5°C.

[0133] S7. According to the requirement of 7% solid content of the polymer material, the total amount of terephthaloyl chloride added is calculated by the reaction equation, and 98.5% of the theoretical total mass of terephthaloyl chloride (TPC), i.e. 38.340 kg, is added into the polymerization kettle for prepolymerization.

[0134] S8. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.584 kg, was added into the polymerization reactor in three portions to carry out telomerization reaction.

[0135] S9, sampling and testing, the dynamic viscosity is 105,000 centipoise.

[0136] S10. The output of the reaction by-product HCL was calculated according to the polymerization reaction equation, corresponding to the input of 8.66 kg of Ca(OH)2 (anhydrous calcium hydroxide). The reaction was continued with stirring for 0.5 hours. The dynamic viscosity was detected by sampling and was 98,000 centipoise.

[0137] S11, filtering and degassing the obtained polymer spinning slurry and then transferring it into a spinning section storage tank.

[0138] S12, the polymerized spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000 dtex, and then initially formed in a coagulation bath, and plasticized and stretched by a traction roller, with a stretching ratio of 100%, and the coagulation liquid is an aqueous solution with a DMAC content of 50%.

[0139] S13, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 140°C.

[0140] S14, the reeled nascent fibers continuously enter the heat treatment drying tunnel through the unwinder and the traction rollers, and the nascent fibers are heat-stretched by controlling the stretching ratio by traction before and after the heat treatment drying tunnel. The length of the heat treatment drying tunnel is 10 meters, the temperature is 450°C, and the spinning speed is 20 meters / minute. In the state where no filaments are generated, the maximum stretching ratio applied by the front and rear five rollers is 45%.

[0141] S15. After stretching, a finished fiber with a line density of 1014 dtex is obtained.

[0142] S16. The test results are shown in Table 5 below.

[0143] Table 5

[0144]

[0145] Comparative Example 1

[0146] In this embodiment, as a comparative example of the present invention, a method for preparing a common heterocyclic aramid fiber is disclosed, comprising the following steps:

[0147] S1. Add 781 L of DMAC (dimethylacetamide) solvent having a water content of 123 ppm into a 1000 L polymerization reactor.

[0148] S2. LiCl (anhydrous lithium chloride) weighing 28.5 kg, which had been vacuum dried at 230° C. for 1 hour, was added into the polymerization kettle containing the solvent. That is, the content of LiCl (anhydrous lithium chloride) in the solvent system was about 3.5%.

[0149] S3. After stirring and dissolving in the polymerization kettle for 0.5 hours, the moisture content was tested and the moisture content was 279 ppm.

[0150] S4. According to the requirement of 5% solid content of polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) to p-phenylenediamine (PPDA) is 1:1. The material addition amount is calculated by the reaction equation, and 16.329 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and 7.873 kg of p-phenylenediamine (PPDA) are successively added to the polymerization kettle. Stirring and dissolving are started for 2-4 hours, and the polymerization kettle is controlled at 35°C.

[0151] S5. Cool the materials in the polymerization kettle through the polymerization kettle jacket to 0-5°C.

[0152] S6. According to the requirement of 5% solid content of the polymer material, the total amount of terephthaloyl chloride added is calculated by the reaction equation, and 98.5% of the theoretical total mass of terephthaloyl chloride (TPC), i.e. 29.153 kg, is added into the polymerization kettle for prepolymerization.

[0153] S7. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.444 kg, was added into the polymerization reactor in three portions to carry out telomerization reaction.

[0154] S8. Sampling and testing, the dynamic viscosity is 95,000 centipoise.

[0155] S9. Calculate the output of the reaction by-product HCL according to the polymerization reaction equation, corresponding to the input of 7.45 kg of Ca(OH)2 (anhydrous calcium hydroxide). Continue stirring the reaction for 0.5 hours, and take a sample to detect the dynamic viscosity, which is 79,000 centipoise.

[0156] S10, filtering and degassing the obtained polymer spinning slurry and then transferring it into a spinning section storage tank.

[0157] S11, the polymerized spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000 dtex, and then initially formed in a coagulation bath, and plasticized and stretched by a traction roller, with a stretching ratio of 50%, and the coagulation liquid is an aqueous solution with a DMAC content of 50%.

[0158] S12, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 140°C.

[0159] S13, the reeled nascent fibers continuously enter the heat treatment drying tunnel through the unwinder and the traction rollers, and the nascent fibers are heat-stretched by controlling the stretching ratio in the front and rear traction of the heat treatment drying tunnel. The length of the heat treatment drying tunnel is 10 meters, the temperature is 450°C, and the spinning speed is 20 meters / minute. In the state where no filaments are generated, the maximum stretching ratio applied by the front and rear five rollers is 10%.

[0160] S14, after stretching and molding, a finished fiber with a line density of 1021 dtex is obtained.

[0161] S15. The test results are shown in Table 6 below.

[0162] Table 6

[0163]

[0164] Comparative Example 2

[0165] In this embodiment, as a comparative example of the present invention, a method for preparing heterocyclic aramid fiber with high elongation is disclosed, comprising the following steps:

[0166] S1. Add 781 L of DMAC (dimethylacetamide) solvent with a water content of 99 ppm into a 1000 L polymerization kettle.

[0167] S2. LiCl (anhydrous lithium chloride) weighing 28.5 kg, which had been vacuum dried at 230° C. for 1 hour, was added into the polymerization kettle containing the solvent. That is, the content of LiCl (anhydrous lithium chloride) in the solvent system was about 3.5%.

[0168] S3. After stirring and dissolving in the polymerization kettle for 0.5 hour, the moisture content was tested and the moisture content was 259 ppm.

[0169] S4. According to the requirement of 7% solid content of polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) to 4,4'-diaminodiphenyl ether (4,4-ODA) is 1:2. The material addition amount is calculated by the reaction equation, and 9.332 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and 16.664 kg of 4,4'-diaminodiphenyl ether (4,4-ODA) are added into the polymerization kettle.

[0170] S5. According to the requirement of 7% solid content of polymer material, the molar ratio of p-phenylenediamine (PPDA) to 4,4'-diaminodiphenyl ether (4,4-ODA) is 1:1. The material addition amount is calculated by the reaction equation. 8.999 kg of p-phenylenediamine (PPDA) is added to the polymerization kettle. Stirring and dissolving is started for 2-4 hours. The temperature of the polymerization kettle is controlled at 35°C.

[0171] S6. Cool the materials in the polymerization kettle through the polymerization kettle jacket to 0-5°C.

[0172] S7. According to the requirement of 7% solid content of the polymer material, the total amount of terephthaloyl chloride added is calculated by the reaction equation, and 98.5% of the theoretical total mass of terephthaloyl chloride (TPC), i.e. 41.651 kg, is added into the polymerization kettle for prepolymerization.

[0173] S8. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.635 kg, was added into the polymerization reactor in three portions to carry out telomerization reaction.

[0174] S9, sampling and testing, the dynamic viscosity is 94,000 centipoise.

[0175] S10. Calculate the output of the reaction by-product HCL according to the polymerization reaction equation, corresponding to the input of Ca(OH)2 (anhydrous calcium hydroxide) 10.64 kg, continue stirring the reaction for 0.5 hours, and take a sample to detect the dynamic viscosity of 88,000 centipoise.

[0176] S11, filtering and degassing the obtained polymer spinning slurry and then transferring it into a spinning section storage tank.

[0177] S12, the polymerized spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000dtex, and then initially formed in a coagulation bath, and plasticized and stretched by a traction roller, with a stretching ratio of 40%, and the coagulation liquid is an aqueous solution with a DMAC content of 50%.

[0178] S13, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 140°C.

[0179] S14, the reeled spun fibers continuously enter the heat treatment drying tunnel through the unwinder and the traction rollers, and the spun fibers are heat-stretched by controlling the stretching ratio before and after the heat treatment drying tunnel. The heat treatment drying tunnel is 10 meters long, the temperature is 450°C, and the spinning speed is 20 meters / minute. In the state where no filaments are generated, the maximum stretching ratio applied by the front and rear five rollers is 25%.

[0180] S15. After stretching, a finished fiber with a line density of 1009 dtex is obtained.

[0181] S16. The test results are shown in Table 7 below.

[0182] Table 7

[0183]

[0184] Comparative Example 3

[0185] In this embodiment, as a comparative example of the present invention, a production process of a heterocyclic aramid fiber with high elongation is disclosed, comprising the following steps:

[0186] S1. Add 781 L of DMAC (dimethylacetamide) solvent with a water content of 99 ppm into a 1000 L polymerization kettle.

[0187] S2. LiCl (anhydrous lithium chloride) weighing 28.5 kg, which had been vacuum dried at 230° C. for 1 hour, was added into the polymerization kettle containing the solvent. That is, the content of LiCl (anhydrous lithium chloride) in the solvent system was about 3.5%.

[0188] S3. After stirring and dissolving in the polymerization kettle for 0.5 hour, the moisture content was tested and the moisture content was 260ppm.

[0189] S4. According to the requirement of 7% solid content of polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) to 3,4'-diaminodiphenyl ether (4,4-ODA) is 1:1. The material addition amount is calculated by the reaction equation, and 14.336 kg of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) and 12.800 kg of 4,4'-diaminodiphenyl ether (4,4-ODA) are added into the polymerization kettle.

[0190] S5. According to the requirement of 7% solid content of polymer material, the molar ratio of p-phenylenediamine (PPDA) to 4,4'-diaminodiphenyl ether (4,4-ODA) is 1.2:1. The material addition amount is calculated by the reaction equation. 8.294 kg of p-phenylenediamine (PPDA) is added to the polymerization kettle, and stirring and dissolving is started for 2-4 hours. The temperature of the polymerization kettle is controlled at 35°C.

[0191] S6. Cool the materials in the polymerization kettle through the polymerization kettle jacket to 0-5°C.

[0192] S7. According to the requirement of 7% solid content of the polymer material, the total amount of terephthaloyl chloride added is calculated by the reaction equation, and 98.5% of the theoretical total mass of terephthaloyl chloride (TPC), i.e. 40.950 kg, is added into the polymerization kettle for prepolymerization.

[0193] S8. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.624 kg, was added into the polymerization reactor in three portions to carry out telomerization reaction.

[0194] S9, sampling and testing, the dynamic viscosity is 81,000 centipoise.

[0195] S10. Calculate the output of the reaction by-product HCL according to the polymerization reaction equation, corresponding to the input of 10.50 kg of Ca(OH)2 (anhydrous calcium hydroxide), continue stirring the reaction for 0.5 hours, and take a sample to detect the dynamic viscosity of 77,000 centipoise.

[0196] S11, filtering and degassing the obtained polymer spinning slurry and then transferring it into a spinning section storage tank.

[0197] S12, the polymerized spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000 dtex, and then initially formed in a coagulation bath, and plasticized and stretched by a traction roller, with a stretching ratio of 30%, and the coagulation liquid is an aqueous solution with a DMAC content of 50%.

[0198] S13, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 140°C.

[0199] S14, the reeled spun fibers continuously enter the heat treatment drying tunnel through the unwinder and the traction rollers, and the spun fibers are heat-stretched by controlling the stretching ratio before and after the heat treatment drying tunnel. The heat treatment drying tunnel is 10 meters long, the temperature is 450°C, and the spinning speed is 20 meters / minute. When no filaments are generated, the maximum stretching ratio applied by the front and rear five rollers is 15% (similarly).

[0200] S15. After stretching, a finished fiber with a line density of 1020 dtex is obtained.

[0201] S16. The test results are shown in Table 8 below.

[0202] Table 8

[0203]

[0204] Table 9 is obtained by statistically analyzing the data of the embodiments and comparative examples.

[0205] Table 9

[0206]

[0207] It can be seen from the above data that the elongation of the heterocyclic aramid fiber with high productivity of the present invention is ≥6.0%, which is more than 50% higher than the elongation of 3%-4% of the general heterocyclic aramid fiber.

[0208] In Comparative Example 1, 4,4'-diaminodiphenyl ether (4,4-ODA) was not added, and high-multiple stretching could not be achieved by heat treatment. In Comparative Example 2, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (R3) to 4,4'-diaminodiphenyl ether (4,4-ODA) was less than 1, and the stretching ratio of the front and rear traction rollers was low during high-multiple stretching by heat treatment. In Comparative Example 3, the molar ratio of 4,4'-diaminodiphenyl ether (4,4-ODA) to phenylenediamine (PPDA) was less than 1, and the stretching ratio of the front and rear traction rollers was low during high-multiple stretching by heat treatment, and no good effect could be achieved.

[0209] During the production process, the introduction of new polymerized materials and high-multiple stretching during spinning heat treatment enable the product to have a tensile strength of no less than 3.5Gpa while greatly improving its elongation. The product has a good appearance and the quality stability of the finished fiber is high, which is at the leading level both at home and abroad.

[0210] This method does not increase the production cost. The introduced fourth monomer 4,4'-diaminodiphenyl ether (4,4-ODA) is cheap and can replace part of the feed amount of 2-(4-aminophenyl)-5-aminobenzimidazole (R3), thereby reducing the cost of product raw materials. Only by optimizing part of the spinning production process, the stable production of high-elongation heterocyclic aramid fibers can be achieved, which is of great value and significance to the development of the entire aramid fiber manufacturing industry.

[0211] The above are the implementation methods listed in this embodiment, but this embodiment is not limited to the above optional implementation methods. Those skilled in the art can arbitrarily combine the above methods to obtain other various implementation methods. Anyone can derive other various forms of implementation methods under the inspiration of this embodiment. The above specific implementation methods should not be understood as limiting the scope of protection of this embodiment. The scope of protection of this embodiment shall be based on the definition in the claims, and the description can be used to interpret the claims.

Claims

1. A method for preparing heterocyclic aramid fiber with high elongation, characterized in that: Using 4,4'-diaminodiphenyl ether (4,4-ODA), 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine as diamine monomers, and using terephthaloyl chloride as a diacyl chloride monomer, the diamine monomers are stirred and dissolved in a solvent system at 30°C-40°C for 1-5 hours, and a polymerized spinning slurry is prepared using the diamine monomers; The method for preparing the polymer spinning slurry comprises the following steps: The preparation is carried out by preparing the solvent system, measuring the preparation amount, detecting the moisture content, dissolving the diamine monomer, cooling, prepolymerizing, telomerizing and neutralizing to reduce viscosity, wherein the cooling is to 0-5°C; The molar ratio of the 4,4'-diaminodiphenyl ether (4,4-ODA) to 2-(4-aminophenyl)-5-aminobenzimidazole is ≤1 and ≥0.5, and the molar ratio of the 4,4'-diaminodiphenyl ether (4,4-ODA) to p-phenylenediamine is ≥1; The polymerized spinning slurry is filtered, degassed, metered and extruded, coagulated, plasticized, stretched, washed and dried to obtain raw fibers; The raw fiber is subjected to heat treatment and high-multiple stretching to obtain a product; The heat treatment high-multiple stretching: the dried raw fiber is sent to a heat treatment drying tunnel, and the speed difference of the front and rear traction rollers of the heat treatment drying tunnel is used to heat treat the raw fiber with high-multiple stretching, the heat treatment drying tunnel is protected by nitrogen, the heat treatment temperature is controlled at 400-500°C, and the stretching ratio of the front and rear traction rollers is 30-60%.

2. The method for preparing heterocyclic aramid fiber with high elongation according to claim 1, characterized in that: The solid content of the polymer spinning slurry is controlled at 5-7%.

3. A heterocyclic aramid fiber with high elongation, characterized in that: The fiber is prepared by the method for preparing heterocyclic aramid fiber with high elongation as described in any one of claims 1 to 2.

Citation Information

Patent Citations

  • Production process of aramid fiber spinning solution containing benzimidazole

    CN116121902A

  • Yarn on the basis of aromatic heterocyclic copolyamide with improved elastic properties and method of its production

    RU2659975C1